Accuracy and adaptation of 3D printed zirconia crowns: A review of current methodologies - Pinelli, Ligia Antunes Pereira [UNESP]; Ferreira, Izabela; Cândido dos Reis, Andrea (Elsevier, 2025)
Statement of problem: The 3-dimensional (3D) printing of polymers and metals is a reality in dentistry; however, despite the advances, the printing of ceramic crowns is still in its infancy. Purpose: The purpose of this review was to examine studies that evaluated the accuracy and adaptation of zirconia crowns produced by additive manufacturing with an emphasis on 3D printing. Material and methods: Electronic databases (Embase, PubMed, SCOPUS, Web of Science, and Google Scholar) were searched between February and March 2024 using the keywords zirconium, zirconium oxide, crowns, 3D printing, additive manufacturing, stereolithography, vat polymerization, digital light processing, nanoparticle jetting, lithography-based ceramic manufacturing, accuracy, trueness, and precision, augmented by manual searches. The eligibility criteria included articles only in English and published in peer-reviewed journals. Results: The database search resulted in 136 articles, reduced to 52 after duplicates were eliminated. After abstract reading and the application of the exclusion criteria, 14 articles remained to be read in full. All studies showed a low risk of bias. Conclusions: The main printing techniques for zirconia crowns include material jetting and vat polymerization, which generally allow crown manufacture with accuracy and marginal adaptation within the clinically accepted range and close to that of milled crowns.